The impact of integrated urban and rural resident basic medical insurance on health service equity: Evidence from China - Li, Qiaosheng; Zhang, Lanyue; Jian, Weiyan (Frontiers in Public Health, 2023)
Background Many countries and regions worldwide are improving their healthcare systems through the integration and unification of health insurance programs covering different groups of people. In China, the past 10 years has been the time when Chinese government promote the Urban and Rural Residents Basic Medical Insurance (URRBMI) by integrating the Urban Residents' Basic Medical Insurance (URBMI) and New Rural Cooperative Medical Scheme (NRCMS). Objectives To evaluate the impact of the URRBMI on equity in relation to health services. Methods The quantitative data used in this study were obtained from the CFPS 2014–2020 database, and all respondents with health insurance type UEBMI, URBMI, and NRCMS were included. UEBMI respondents were set as the control group and URBMI or NRCMS as the intervention group, and a DID method model was used to analyze the impact of integrating health insurance on health service utilization, costs and health status. Heterogeneity analysis was also conducted after stratifying the sample according to income level and chronic disease status. This was done to investigate whether there were differences in the effects of the integrated health insurance program across different social groups. Results The implementation of URRBMI is found to be associated with a significant increase in inpatient service utilization (OR = 1.51, P < 0.01) among rural Chinese residents. Regression results by income stratum show that the utilization of inpatient services increased in rural areas for high-, middle- and low-income groups, with the fastest increase (OR = 1.78, P < 0.05) emerging for low-income groups. Analysis by chronic disease status shows that rural residents with chronic disease are associated with a higher increase in hospitalization rates (OR = 1.64, P < 0.01). Conclusion The implementation of URRBMI is found to have improved health insurance's ability to withstand risks and effectively improve access to health services for rural residents. In this regard, it can be considered as playing a positive role in bridging the gap in health service utilization between rural and urban areas and in improving regional equity.